Analysis of the Influence of Liquidity, Solvency, and Share Price on Company Value in Indonesian State-Owned Enterprises - Masno, Masno; Pratama, Guruh Dwi; Yunita, Yunita (Pt. Anagata Sembagi Education, 2024)
Companies often seek to increase the value of the company over time, because the high value of the company reflected in the stock price will increase the wealth of shareholders. This study aims to analyze the influence of the Current Ratio, Return on Asset (ROA), and Stock Price on Company Value over ten years. The independent variables used are Current Ratio, Return on Asset, and Stock Price while the dependent variable is Company Value. These data were then analyzed using multiples of the regression method involving a statistical test t (partial), statistical test F (simultaneous), and a coefficient of determination test. The results show that the Current Ratio, Return on Asset, and Stock Price partially have a positive and significant effect on the value of the company. significant impact on the Current Ratio, Return on Asset, and Share Price has a significant effect on the company's value. The implication of this research is that understanding the factors that affect firm value can help in designing more effective policies and strategies to improve the company's financial performance and attractiveness in the eyes of investors.